A “REVOLTA DA INEFICIÊNCIA”: OS ACONTECIMENTOS DE JUNHO DE 2013 NO BRASIL E SUAS DESTITUIÇÕES POLÍTICO-TEOLÓGICAS - SOUZA, Daniel Santos (2019)
This doctoral dissertation seeks to rehearse a theological reading cut through and provoked by the destituting potencies in the events of June 2013 in Brazil. In this perspective, “June” is uncoupled to the “constituting power” that pursues a new institutional order and framed in the “security state paradigm” and its relations to neoliberal capitalism. In this way, I understand that these events can be interpreted beyond matters of political-strategic consequences and rather seen as a revolt capable of exposing the anarchy and lawlessness present in the technologies of the “government machine.” For my methodological trajectory, I was interested in “collecting” the images left behind in these events. Through street massages such as graffiti, banners, signs, and flags, I wished to find destituting and inefficient traces in an alliance of bodies that create new habitats in the city. With this outlook, I come to “June” as a political-theological hinge. On the one hand, it reveals the theological signature of the state and presents a profanatory and destituting potential of modern politics. On the other hand, by indicating other modes of political living and by (re)imagining the “sacred” in the State and by “dividing the division” between sacred and profane, June favors processes of revising theological projects, such as Latin American liberation theology. In order to imagines the theological traces of June 2013, I employed as my theoretical reference the work of Italian philosopher Giorgio Agamben (1942-), especially in his project Homo sacer. Together with this, I sought to construct creative tensions between an “inoperant theology” and the theological paradigm of the Exodus, central to liberation theologies that focus on identity (the oppressed subject), sovereignty (the liberating God), the nation/people, the possession of the land, and on the effectiveness of the struggle. My choice for liberation theologies is due to its ties to a spirituality that assumes and is connected to popular struggles and for its interest in reflecting and constructing political projects. These interactions, under the guise of June, can open up possibilities for new uses of politics and in “thinking the unthinkable” as an inefficient theology, oriented, for example, toward the Hebrew conception of sabbath. The reading offered by this dissertation is diagrammatical and it creates certain space for theological expressions with an emphasis on the spirit and the messianic time, in liberation, god’s immanence, and on the grace of the “community to come.” Finally, exploring an inefficient dimension of writing, the dissertation concludes with an artistic intervention in the streets of the city of São Paulo, entitled: “traces of god in the traces of June.”